PEDAGOGICAL FOUNDATIONS FOR THE USE OF DIGITAL TECHNOLOGIES IN TEACHING GENERAL ASTRONOMY AT PEDAGOGICAL UNIVERSITIES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article examines the pedagogical and methodological foundations for the effective use of digital technologies in teaching general astronomy to students of pedagogical universities. It analyzes the didactic potential of interactive computer models, digital simulators, and multimedia tools in enhancing the effectiveness of the educational process and fostering students' independent learning. The study emphasizes that integrating digital technologies into astronomy education enables the visualization of complex spatial phenomena, promotes analytical thinking, scientific observation, and reflective learning skills among students. The research also highlights the need for localized digital resources and proposes the development of digital learning environments tailored to the Uzbek educational context.